Economic growth and sustainability: An analysis of the Environmental Kuznets Curve on the Legal Amazon - Wakim, Vasconcelos Reis; Roma, Jaques Otto; Magalhães, Elizete Aparecida de (Revista Agrogeoambiental, 2021)
The objective of this work was to analyze how deforestation of the Legal Amazon (AMZ-L) is affected by the economic growth of the states it covers, from 2000 to 2017. This study is based on the Environmental Kuznets Curve theory (EKC), proposed by Grossman and Krueger (1991). We used the panel data method considering the fixed effects to answer the research problem. The hypothesis of the EKC, in fact, happens in the initial stage, showing that, with the increase in income, deforestation rates drop, causing the curve to reverse, taking an inverted “U” shape. However, at high-income levels, deforestation increases again, thus the curve takes an “N” shape. Considering this scenario, we can conclude that the increase in income alone does not guarantee deforestation reduction. However, we must emphasize that deforestation rates are lower than in the initial stage at high-income levels, showing the government intervention is needed.